Subsidy Reforms and Their Implications for Green Investment in Indonesia’s Renewable Energy Market - Nurarma Sari; Adinda Kaniya (Generasi Sains Indonesia, 2025)
This study explores the implications of subsidy reforms on green investments in Indonesia's renewable energy market, with a focus on understanding how changes in subsidy structures can support the transition from fossil fuels to renewable energy. A mixed-methods approach was used, combining quantitative data analysis on investment trends and subsidy allocation, along with qualitative interviews with key stakeholders. The findings reveal that while fossil fuel subsidies have been gradually reduced, the impact on renewable energy investments has been modest, particularly in emerging sectors like solar and wind. Geothermal and hydropower sectors received the majority of the subsidies, despite the higher potential for solar and wind. The study also finds that political resistance and the lack of clear policy stability hinder the effective implementation of subsidy reforms. Social support programs have been introduced but have not fully mitigated the regressive impacts of higher energy prices. The results suggest that more aggressive and targeted financial incentives are needed to boost green investments, alongside comprehensive long-term policy reforms. The study contributes to the understanding of subsidy reforms in the context of energy transition and highlights areas for further research, including the role of carbon pricing mechanisms and the effectiveness of social programs in promoting energy justice.